Designing Probability Learning Utilizing Ice Cream Sticks: An RME-Based Approach - Choirunisa, Choirunisa; Zulkardi, Zulkardi; Susanti, Ely; Meryansumayeka, Meryansumayeka (Universitas Islam Negeri Sunan Kudus, 2026)
This study aims to design a learning trajectory for probability using the context of ice cream sticks through the Realistic Mathematics Education (RME) approach. The method employed is design research of the validation study type, consisting of preliminary design, teaching experiment, and retrospective analysis. Data were collected through student activity sheets and interviews involving 31 ninth-grade students. The results indicate that the designed learning trajectory facilitates a gradual shift in students’ reasoning from informal to formal probability concepts. At the initial stage, students identified possible outcomes through concrete activities involving colored sticks. They then constructed sample spaces by listing outcomes and representing them using tables and tree diagrams in two-stage experiments. At the model-for stage, students were able to determine the total number of possible outcomes and distinguish between types of events, although some difficulties were observed in understanding sampling with replacement. At the formal stage, most students expressed probability as a ratio of favorable outcomes to the total sample space and represented it using symbolic notation. Retrospective analysis shows that the Hypothetical Learning Trajectory (HLT) is valid in supporting students’ conceptual development, particularly in bridging contextual understanding and formal representation. However, teacher guidance remains necessary in constructing complete sample spaces and interpreting probability as a ratio. This study contributes a practical context-based learning trajectory for implementing RME in probability learning. Penelitian ini bertujuan untuk mendesain lintasan belajar (learning trajectory) pada materi peluang menggunakan konteks stik es krim melalui pendekatan Realistic Mathematics Education (RME). Metode yang digunakan adalah design research tipe validation study yang terdiri dari tahap preliminary design, teaching experiment, dan retrospective analysis. Data dikumpulkan melalui lembar aktivitas siswa dan wawancara dengan melibatkan 31 siswa kelas IX. Hasil penelitian menunjukkan bahwa lintasan belajar yang dirancang mampu mendukung pergeseran penalaran siswa secara bertahap dari konsep peluang informal menuju formal. Pada tahap awal, siswa mengidentifikasi kemungkinan hasil melalui aktivitas konkret mengenali warna stik. Selanjutnya, siswa mengonstruksi ruang sampel dengan menuliskan seluruh kemungkinan dan merepresentasikannya dalam bentuk tabel serta diagram pohon pada percobaan dua tahap. Pada tahap model-for, siswa mulai mampu menentukan banyaknya seluruh kemungkinan kejadian dan membedakan jenis-jenis kejadian, meskipun masih ditemukan kesulitan dalam memahami konsep pengambilan dengan pengembalian. Pada tahap formal, sebagian besar siswa mampu menyatakan peluang sebagai perbandingan antara banyaknya kejadian yang diinginkan dengan seluruh kemungkinan serta menuliskannya dalam bentuk notasi simbolik. Hasil retrospective analysis menunjukkan bahwa Hypothetical Learning Trajectory (HLT) yang dikembangkan valid dalam mendukung perkembangan pemahaman konsep siswa, khususnya dalam menjembatani transisi dari penalaran kontekstual menuju representasi matematis formal. Namun demikian, intervensi guru melalui pertanyaan penuntun masih diperlukan, terutama dalam membantu siswa menyusun ruang sampel secara lengkap dan memahami peluang sebagai suatu perbandingan. Penelitian ini menghasilkan desain lintasan belajar materi peluang berbasis konteks yang praktis dan dapat diterapkan dalam pembelajaran berbasis RME di kelas.